2016
DOI: 10.1038/gene.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune risk variants in ERAP2 are associated with gene-expression levels in thymus

Abstract: Genetic polymorphisms in the endoplasmic reticulum aminopeptidase (ERAP)1 and ERAP2 genes have been associated with several autoimmune diseases (AIDs) at a genome-wide significance level. In this study, we performed a cis expression quantitative trait locus (eQTL) screen to investigate whether seven fine-mapped AID single-nucleotide polymorphisms (SNPs) in the ERAP-region influence the gene-expression levels of ERAP1 and ERAP2 in thymus. After quality control, we identified six significant eQTLs. We further as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 169 publications
(251 reference statements)
0
8
0
Order By: Relevance
“…However, the haplotype with this variant contains hundreds of other linked variants with significant population variation and harbors a second conditional ERAP2 eQTL in GTEx v8 LCLs. Moreover, several prior studies have demonstrated associations between ERAP2 expression and cis-variation independently of NMD, although linkage limited the resolution of functional studies ( 33, 45, 49, 50 ). Taken together, these results suggest that ERAP2 is regulated by a complex multi-allelic structure which operates via both gene expression and splicing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the haplotype with this variant contains hundreds of other linked variants with significant population variation and harbors a second conditional ERAP2 eQTL in GTEx v8 LCLs. Moreover, several prior studies have demonstrated associations between ERAP2 expression and cis-variation independently of NMD, although linkage limited the resolution of functional studies ( 33, 45, 49, 50 ). Taken together, these results suggest that ERAP2 is regulated by a complex multi-allelic structure which operates via both gene expression and splicing.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most complex multi-variant colocalizations was identified at the ERAP2 locus, which is an aminopeptidase that has been functionally implicated in both Irritable Bowel Disease and Crohn's Disease and for which we observe strong eQTL-GWAS colocalization (45)(46)(47). However, unlike AHI1, we detected six putative causal variants of which five are directionally concordant with eQTL effect along with a significant haplotype effect.…”
Section: Experimental Fine-mapping Of Complex Trait Associationsmentioning
confidence: 97%
See 1 more Smart Citation
“…ERAP2 encodes for endoplasmic reticulum aminopeptidase 2, which is responsible for trimming peptides to optimal sizes for antigen presentation by MHC class I [53]. ERAP2 variants are associated with various immune diseases, including psoriasis [54,55]. Together, these results showed that the protective haplotype (rs2549797-G and rs2248374-G) almost certainly caused NMD to decrease ERAP2 gene expression, which appeared to reduce the risk of psoriasis.…”
Section: Candidate Functional Variants Newly Identified In Gene Regionsmentioning
confidence: 87%
“…We have previously reported autoimmune disease associated expression quantitative trait loci (eQTL) in whole human thymus [27, 28]. As the thymic tissue is composed of 98% thymocytes and only 2% APCs [29], it is conceivable that the expression of these eQTL genes (eGenes) originated from the developing T cells.…”
Section: Resultsmentioning
confidence: 99%